In Search of Methodology to Analyze Production Data Using Type Curve - KRITIA AUDHY (NIM 12205050); Pembimbing: Dr.Ir.Taufan Marhaendrajana, NURRIFFAR
Further development of produced oil field requires information about the effectiveness of well drainage area. The well effectiveness can be determined from drainage volume compared to reservoir volume. In this case, drainage volume is Initial Oil In Place in drainage area. Drainage volume from oil well can be affected by reservoir discontinuity and water breakthrough. This paper attempts to get more information about Initial Oil In Place from well drainage using well production data such as oil rate and water rate without using pressure data. Developed method has the form of type curve between water cut and recovery factor done empirically. It is expected that this method can be used easily by available data without needing certain tests. Therefore this method is useful as initial evaluation quickly in further development of a field.